Regulatory Federalism and Broadband Divergence: Implications of Invoking Europe in the Making of Canadian Telecom Policy - Reza Rajabiun; Catherine Middleton (Intereconomics, 2017)
Invocations of Europe are increasingly evident in Canadian debates about wholesale broadband access, consumer protection, network neutrality and basic service policies. While some stakeholders in Canadian debates point to national and local approaches in Europe that appear to have been relatively successful in fostering broadband infrastructure development, others suggest that Europe is lagging behind and Canada should avoid Europe's purported policy errors.
Keywords: 330